Schedule management and meeting the demands of an architecture and urban planning office located in the state of Rio de Janeiro - BR - Fonseca, Isabela Rocha Lima Palmer; Gonçales Filho, Manoel (Brazilian Journal of Production Engineering, 2024)
This work involves managing the schedules of an architecture and urban planning office located in the State of Rio de Janeiro, Brazil. The routine, demand and management of the entire office were studied. The objective was to develop and implement an efficient methodology for distributing teams and tasks within the schedule, aiming to optimize the workflow, reduce waste and increase transparency and organizational efficiency. For the methodology, a qualitative approach was used and the technical procedure was the case study. The results were better structuring of management models in the office, combined with methods, software, graphics and programs that enable a clear and didactic reading of management, making it transparent and readable by the entire team.
Keywords: Strategies; Real state market; Administration; Crisis.; Construction management; BIM programs